HUBUNGAN ANTARA GRATITUDE DENGAN PSYCHOLOGICAL WELL-BEING PADA MAHASISWA PENERIMA BEASISWA UNIVERSITAS X DI PRINGSEWU - Agustin, Vera; Wigati, Meilia (unprimdn.ac.id, 2024)
Psychological well-being is the state of an individual who is physically and mentally healthy. A form of psychological well-being is a feeling of happiness or satisfaction where the individual can feel that their psychological condition is in good condition. The research objective was to determine the correlation between gratitude and psychological well-being in scholarship students at the X University of Pringsewu. This research employed a quantitative approach and a purposive sampling technique. The sample in this study was 125 students who received scholarships. This research data uses product moment analysis techniques using the Statistical Product and Service Solution (SPSS) 25.0 for Windows program. Based on the results of the product moment analysis (r = 0.773; P = 0.000), this data analysis shows that there is a significant correlation between gratitude and psychological well-being in scholarship students at the X University of Pringsewu. This means that the higher the gratitude towards students, the higher the level of psychological well-being they have. Conversely, students who are less grateful also tend to be less psychologically well-off. Gratitude has a 59,7% coefficient of determination when it comes to psychological well-being.